Stan infrastruktury hydrotechnicznej w aspekcie rozwoju turystyki i transportu wodnego na Kanale Bydgoskim - Galor, Wiesław; Nadolny, Grzegorz; Szatten, Dawid Aleksander (Journal of Education, Health and Sport, 2015)
Galor Wiesław, Nadolny Grzegorz, Szatten Dawid. Stan infrastruktury hydrotechnicznej w aspekcie rozwoju turystyki i transportu wodnego na Kanale Bydgoskim = Conditions of hydrotechnical infrastructure in the aspect of development of tourism and water transport on the Bydgoszcz Canal. Journal of Education, Health and Sport. 2015;5(10):146-157. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32541 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A146-157 https://pbn.nauka.gov.pl/works/660767 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. Stan infrastruktury hydrotechnicznej w aspekcie rozwoju turystyki i transportu wodnego na Kanale Bydgoskim Conditions of hydrotechnical infrastructure in the aspect of development of tourism and water transport on the Bydgoszcz Canal Wiesław Galor, Grzegorz Nadolny, Dawid Szatten Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Instytut Geografii, 85-428 Bydgoszcz, ul. Mińska 15 Streszczenie Kanał Bydgoski, wybudowany w latach 70-tych XVIII wieku, łączy dorzecza Wisły i Odry. Jego unikalne położenie warunkuje rozwój żeglugi śródlądowej w skali regionu oraz Europy Środkowej. W pracy scharakteryzowano stan infrastruktury technicznej oraz warunki hydrologiczne drogi wodnej. Kanał Bydgoski należy do II kategorii dróg wodnych. Projekty realizowane w skali krajowej i europejskiej, przyczyniają się do poprawy stanu infrastruktury wodnej, powodując wzrost atrakcyjności Kanału Bydgoskiego oraz regionu. Słowa kluczowe: żegluga śródlądowa, infrastruktura hydrotechniczna, drogi wodne, Kanał Bydgoski. Abstract Bydgoszcz Canal, built in the 70’s of eighteenth century, connects the Vistula and Oder rivers basins. It’s unique location determines the development of inland shipping in the region and Central Europe scales. The study characterized the state of the technical infrastructure and hydrological conditions of the waterway. Bydgoszcz Canal belongs to the II category of waterways. Projects implemented in national and European level, contribute to the improvement of hydrotechnical infrastructure, causing an increase in the attractiveness of the Bydgoszcz Canal and the region. Key words: inland shipping, hydrotechnical infrastructure, waterways, Bydgoszcz Canal.